Pengolahan Cabai Merah Besar Menjadi Selai - icha; Rivaldi; Aqiedatul Izzah; Muh. Syafi’i Ma’arif; Aisyah Nur Sabina1; Rizky; Sapar (Vivabio: Jurnal Pengabdian Multidisiplin, 2023)
Processing large red peppers into jam. The purpose of the student-entrepreneurship creativity program (PKM-K) is to motivate students to become entrepreneurs in the use of agricultural products which are the main source of Indonesian income. Red chili (Capsicum annum, L) is one of the horticultural plants that has a fairly high economic value and rich in nutrients. The methods of implementing this program are input, process (production), output, and evaluation. The result of the program is input, conducting market surveys to find out market conditions. Next is a feasibility study of the business to be carried out. The last stage is the selection of materials and the provision of premises as well as facilities and infrastructure to support the production process. Process (production), the process of processing large red chili into jam starting from the preparation of ingredients and tools until the processed products in packaging are ready to be marketed. Output, which is a jam product in a jar size of approximately 100 grams that is ready to be used and marketed to consumers. The last is evaluation, at this stage, we will review what shortcomings make consumers dislike the taste or durability of jam when consuming our products. The conclusion of the PKM-K program is that big red chili, which is usually only used as a spice in the main food, can also be another product as a snack, and students learn entrepreneurship by utilizing agricultural products which are a milestone in the Indonesian economy. ABSTRAK Mengolah cabe merah besar menjadi selai. Tujuan program kreativitas mahasiswa-kewirausahaan (PKM-K) adalah memangkitkan motivasi mahasiswa untuk berwirausaha dalam pemanfaatan hasil tani yang menjadi sumber utama pendapatan Indonesia. Cabai merah (Capsicum annum,L) merupakan salah satu tanaman hortikultura yang mempunyai nilai ekonomis cukup tinggi dan kaya akan gizi. Metode pelaksanaan program ini adalah input, proses (produksi), output, dan evaluasi. Hasil program ini adalah input, melakukan survei pasar untuk mengetahui kondisi pasar. Selanjutnya adalah studi kelayakan terhadap usaha yang akan dijalankan. Tahap terakhir adalah pemilihan bahan dan penyediaan tempat serta sarana dan prasarana untuk menunjang proses produksi. Proses (produksi), proses pengolahan cabai merah besar menjadi selai mulai dari persiapan bahan dan alat sampai hasil olahan dalam kemasan siap dipasarkan. Output, yaitu produk selai dalam kemasan toples ukuran kurang lebih 100 g yang siap digunakan dan dipasarkan kepada konsumen. Yang terakhir adalah evaluasi, yaitu tahapan untuk meninjau tentang kekurangan-kekurangan apa saja yang membuat konsumen tidak menyukai cita rasa maupun ketahanan selai saat mengkonsumsi produk kami. Kesimpulan program PKM-K adalah bahwa cabai merah besar yang biasanya hanya digunakan sebagai rempah pada makanan utama, bisa juga menjadi produk lain sebagai cemilan, dan Mahasiswa belajar berwirausaha dengan pemanfaatan hasil tani yang menjadi tonggak ekonomi Indonesia.